2018
DOI: 10.1016/j.eucr.2018.01.009
|View full text |Cite
|
Sign up to set email alerts
|

A case of spontaneous urinary bladder rupture secondary to urinary retention due to an urethral stricture

Abstract: A spontaneous, non-traumatic, urinary bladder rupture is a rare condition. We describe a case of a 23-year-old male with a spontaneous bladder rupture secondary to urinary retention, due to an urethral stricture. He presented to the emergency department with voiding difficulties, severe abdominal pain and renal failure. Abdominal ultrasound revealed large amounts of ascites. After an unsuccessful attempt to place a Foley catheter a cystoscopy was performed which showed an urethral stricture. On CT-cystogram an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 5 publications
0
10
0
2
Order By: Relevance
“…Various medical imaging modalities have been used to diagnose bladder perforations, including ultrasound, abdominal CT, conventional retrograde cystography, and CT-cystography [10] . However, conventional retrograde cystography and CT-cystography are currently the gold standards for bladder perforation diagnosis [11] . Abdominal ultrasound and contrast-enhanced CT with delayed phase have lower sensitivity and specificity than other methods [10] .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Various medical imaging modalities have been used to diagnose bladder perforations, including ultrasound, abdominal CT, conventional retrograde cystography, and CT-cystography [10] . However, conventional retrograde cystography and CT-cystography are currently the gold standards for bladder perforation diagnosis [11] . Abdominal ultrasound and contrast-enhanced CT with delayed phase have lower sensitivity and specificity than other methods [10] .…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have reported that intraperitoneal bladder perforations can be treated with minimally invasive approaches, such as laparoscopic repair or percutaneous peritoneal drainage [12 , 13] . In addition, the treatment of complications, such as hyperkalemia, acidosis, and sepsis, play essential roles [11] . Bladder ruptures that are diagnosed at later stages may be fatal [14] .…”
Section: Discussionmentioning
confidence: 99%
“…Given that our patient had an elevated IPSS score prior to her second bladder perforation, increasing IPSS score is a useful tool to help predict subsequent rupture. Elevated serum creatinine can also be a diagnostic clue as longstanding intraperitoneal urine creatinine after rupture will be reabsorbed into the serum [ 3 , 7 9 ]. Diagnosis can be made with CT cystogram or a traditional cystogram [ 20 , 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…Ultrasound can also make the diagnosis by instillation of saline and air into the bladder [ 11 ]. Cystoscopy is not recommended but can be used to place the urethral catheter in the cases of urethral stricture or false passage [ 16 ]. In our case, retrograde cystography was not performed because of the urinary tract infection, CT scan without contrast allowed us to make the diagnosis, and the exam positivity is due to the defect location which was not plugging during the radiological examination, and the large size of the diverticulum which was always filled with urine despite its perforation, probably because the diverticulum wall was not completely ruptured and because of the small size of the defect.…”
Section: Discussionmentioning
confidence: 99%